Chemoproteomic Profiling Uncovers CDK4-Mediated Phosphorylation of the Translational Suppressor 4E-BP1. Issue 7 (18th July 2019) - Mitchell, Dylan C.; Menon, Arya; Garner, Amanda L.
Summary: Recent estimates of the human proteome suggest there are ∼20, 000 protein-coding genes, the protein products of which contain >145, 000 phosphosites. Unfortunately, in-depth examination of the human phosphoproteome has outpaced the ability to annotate the kinases that mediate these post-translational modifications. To obtain actionable information about phosphorylation-driven signaling cascades, it is essential to identify the kinases responsible for phosphorylating sites that differ across disease states. To fill in these gaps we have developed an unbiased, chemoproteomic approach for identifying high-confidence kinase-substrate interactions with phosphosite specificity. Using this assay, we uncovered the role of cyclin-dependent kinase 4 (CDK4), a clinically validated kinase important for cell-cycle progression, in regulating cap-dependent translation via phosphorylation of the tumor suppressor 4E-BP1. The discovery of this signaling axis sheds light on the mechanisms by which CDK4/6 inhibitors control cell proliferation and constitutes a successful example of kinase discovery using an activity-based, kinase-directed probe. Graphical Abstract: Highlights: Development of a kinase-substrate crosslinking assay A mechanism of CDK4/6 and mTORC1 inhibitor cooperativity in breast cancer cell lines Mechanistic evaluation of an orphan 4E-BP1 phosphorylation site Dissection of 4E-BP1 phosphorylation-dependent c-Myc translation Abstract : Mitchell et al. describe PhAXA, an improved chemoproteomic pipeline for mapping kinase-substrate interactions with phosphorylation-site specificity. Using this assay, the role of CDK4 in phosphorylating 4E-BP1 was identified, thereby influencing mTORC1-inhibitor resistant cap-dependent translation and specifically promoting c-Myc expression.